2022
DOI: 10.1155/2022/9201795
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Quadratus Lumborum Block versus Transversus Abdominis Plane Block in Laparoscopic Surgery: A Randomized Controlled Study

Abstract: Background. After laparoscopic abdominal surgery, we aim to evaluate the analgesic efficiency of US-directed bilateral transversus abdominis plane block (TAPB) and quadratus lumborum block (QLB). Methods. 50 patients aged 18–60 years listed for elective laparoscopic abdomen operation were registered in this study. Cases were randomly allocated into two similar groups: TAPB and QLB groups. The first outcome was the growing morphine consumption on the 1st day postoperatively. The second outcome involved VAS scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Total morphia dosage in 1st 1 day postoperation was significantly less in ESPB and QLBs versus groups C (P value<0.001) and was similar between groups ESPB and QLB. Similar to our findings, Fargaly et al, [23] documented that the median morphine dosage was significantly less in QLB versus TAPB group. In agreement with our findings, Huang and 1 day after surgery, cases underwent US ESPB required significantly less IV opioids (standardized mean difference [SMD] = -2.18; 95% CI -2.76 to -1.61, p< 0.00001).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Total morphia dosage in 1st 1 day postoperation was significantly less in ESPB and QLBs versus groups C (P value<0.001) and was similar between groups ESPB and QLB. Similar to our findings, Fargaly et al, [23] documented that the median morphine dosage was significantly less in QLB versus TAPB group. In agreement with our findings, Huang and 1 day after surgery, cases underwent US ESPB required significantly less IV opioids (standardized mean difference [SMD] = -2.18; 95% CI -2.76 to -1.61, p< 0.00001).…”
Section: Discussionsupporting
confidence: 92%
“…Hematoma didn't occur in any case in the three groups. In the same context, Fargaly et al, [23] reported that Both techniques QLB showed nonsignificant Also, Abd Ellatif and Abdelnaby [19] reported that no block-related or local anesthetic-toxicity-related complications were observed among the intervention groups (QLB and ESPB).…”
Section: Discussionmentioning
confidence: 91%
“…US-TAP Subcostal block is associated with less pain experience and opioid consumption compared with quadratus lumborum [ 78 ]. Between 0 and 6 h postop, the US-TAP subcostal block appeared to be associated with higher pain perception; in contrast, the quadratus lumborum was perceived as more painful between 12 and 24 h [ 97 ]. To view it differently, quadratus lumborum reportedly had lower pain perception, lower cumulative daily Morphine consumption, and longer median time to first analgesic request compared with US-TAP block [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Between 0 and 6 h postop, the US-TAP subcostal block appeared to be associated with higher pain perception; in contrast, the quadratus lumborum was perceived as more painful between 12 and 24 h [ 97 ]. To view it differently, quadratus lumborum reportedly had lower pain perception, lower cumulative daily Morphine consumption, and longer median time to first analgesic request compared with US-TAP block [ 97 ]. Therefore, further quantification is needed to clarify the pattern of analgesic consumption during different TAP blockade procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation